A bidirectional competitive interaction between circHomer1 and Homer1b within the orbitofrontal cortex regulates reversal learning - Hafez, Alexander K.; Zimmerman, Amber J.; Papageorgiou, Grigorios; Chandrasekaran, Jayapriya; Amoah, Stephen K.; Lin, Rixing; Lozano, Evelyn; Pierotti, Caroline; Dell’Orco, Michela; Hartley, Brigham J.; Alural, Begüm; Lalonde, Jasmin; et al. (Cell reports (Cambridge), 2022)
Although circular RNAs (circRNAs) are enriched in the brain, their relevance for brain function and psychiatric disorders is poorly understood. Here, we show that circHomer1 is inversely associated with relative HOMER1B mRNA isoform levels in both the orbitofrontal cortex (OFC) and stem-cell-derived neuronal cultures of subjects with psychiatric disorders. We further demonstrate that in vivo circHomer1 knockdown (KD) within the OFC can inhibit the synaptic expression of Homer1b mRNA. Furthermore, we show that circHomer1 directly binds to Homer1b mRNA and that Homer1b-specific KD increases synaptic circHomer1 levels and improves OFC-mediated behavioral flexibility. Importantly, double circHomer1 and Homer1b in vivo co-KD results in a complete rescue in circHomer1-associated alterations in both chance reversal learning and synaptic gene expression. Lastly, we uncover an RNA-binding protein that can directly bind to circHomer1 and promote its biogenesis. Taken together, our data provide mechanistic insights into the importance of circRNAs in brain function and disease. [Display omitted] •Expression of circHomer1 is inversely associated with relative HOMER1B mRNA levels•CircHomer1 and Homer1b bind to each other and inhibit each other's synaptic expression•In vivo KD of Homer1b improves OFC-mediated chance reversal learning•Co-KD of Homer1b and circHomer1 restores chance reversal learning Through in vivo circRNA and mRNA isoform-specific knockdown in mouse orbitofrontal cortex (OFC), Hafez et al. elucidate the antagonistic interaction between the psychiatric-disease-associated circHomer1 and Homer1b mRNA and their opposing effects on OFC-mediated reversal learning.